A new species of Oratosquillina Manning, 1995 (Crustacea : Stomatopoda : Squillidae) from the Indo-West Pacific region with a key to the genus - Ahyong, Shane T.; Chan, Tin-Yam (Zootaxa, 2008)
A new species of stomatopod crustacean, Oratosquillina nordica sp. nov. is described from the Indo-West Pacific region (type locality: Taiwan). It is most similar to O. quinquedentata (Brooks, 1886), with which it has been confused. Oratosquillina quinquedendata is presently known only from the southern hemisphere, and most of its northern hemisphere records are referable to O. nordica. Records of O. quinquedentata from India and Sri Lanka require confirmation, possibly representing a third species. A key to the species of Oratosquillina is provided.